High yield lipase-catalyzed synthesis of Engkabang fat esters for the cosmetic industry - Abd. Rahman, Nur Fariza; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar (Elsevier, 2011)
Engkabang fat esters were produced via alcoholysis reaction between Engkabang fat and oleyl alcohol, catalyzed by Lipozyme RM IM. The reaction was carried out in a 500 ml Stirred tank reactor using heptane and hexane as solvents. Response surface methodology (RSM) based on a four-factor-five-level Central composite design (CCD) was applied to evaluate the effects of synthesis parameters, namely temperature, substrate molar ratio (oleyl alcohol: Engkabang fat), enzyme amount and impeller speed. The optimum yields of 96.2% and 91.4% were obtained for heptane and hexane at the optimum temperature of 53.9 °C, impeller speeds of 309.5 and 309.0 rpm, enzyme amounts of 4.82 and 5.65 g and substrate molar ratios of 2.94 and 3.39:1, respectively. The actual yields obtained compared well with the predicted values of 100.0% and 91.5%, respectively. Meanwhile, the properties of the esters show that they are suitable to be used as ingredient for cosmetic applications.